2017
DOI: 10.1111/1346-8138.13974
|View full text |Cite
|
Sign up to set email alerts
|

Increased endocan expression in lesional skin and decreased endocan expression in sera in atopic dermatitis

Abstract: Endocan is a novel human endothelial cell-specific molecule and is mainly expressed in endothelial cells in various tissues. Endocan has the capacity to inhibit leukocytes binding to the vascular endothelium. It also can promote the angiogenesis alongside vascular endothelial growth factor A. Through these functions, endocan has been implicated in the pathogenesis of various inflammatory diseases. To investigate the possible roles of endocan in atopic dermatitis (AD), we examined endocan expression in lesional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…19 Additionally, angiogenesis is a hallmark of chronic inflammatory skin diseases and plays a major role in both psoriasis and atopic dermatitis. 20 So, in line with our findings, Suzuki et al, 21 reported that endocan expression in lesional skin of atopic dermatitis was significantly higher than those in normal skin by immunohistochemistry.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…19 Additionally, angiogenesis is a hallmark of chronic inflammatory skin diseases and plays a major role in both psoriasis and atopic dermatitis. 20 So, in line with our findings, Suzuki et al, 21 reported that endocan expression in lesional skin of atopic dermatitis was significantly higher than those in normal skin by immunohistochemistry.…”
Section: Discussionsupporting
confidence: 91%
“…The sum of these three severity parameters was then calculated for each skin section and was multiplied by the area score for that area and by weight of respective section (0.1 for head, 0.2 for upper limb, 0.3 for trunk, and 0.4 for lower limb). The final formula for PASI score is given as: PASi = 0.1 (eh + ih + Dh) Ah + 0.2 (eu + iu + Du) Au + 0.3 (et + it + Dt) At + 0.4 (el + il + Dl) Al [21].PASI ranged from 0 (no disease) to 72 (maximal). A PASI score <7 denoted mild psoriasis, from 7 to 12 denoted moderate and more than 12 meant severe form of psoriasis.…”
Section: Patients and Me Thodsmentioning
confidence: 99%
“…Future studies of endocan-1 in psoriatic skin could therefore be of interest. Suzuki et al have reported reduced systemic endocan-1 levels in patients with atopic dermatitis, as well as an increment in endocan-1 in atopic dermatitis skin lesions, where it was expressed by keratinocytes and dermal endothelial cells (240). This is interesting in relation to the decreased sVEGFR1 levels seen in Study III.…”
Section: Departments Of Dermatology At Linköping University Hospitalmentioning
confidence: 57%
“…It may be speculated that the reduced endocan-1 levels may be the result of a feedback loop stemming from the increased levels of ICAM-1, and that the low levels of endocan-1 may result in a lack of inhibition of leukocyte transmigratory responses. Such a mechanism has also been proposed in atopic dermatitis [22].…”
Section: Discussionmentioning
confidence: 84%